Talent management: a case study of Namibia's Directorate of Civil Aviation (DCA) in securing talent for aviation safety, 2008 to 2014 - Simataa, George (Rhodes University, Faculty of Commerce, Rhodes Business School, 2017)
This study is about talent management, focusing on a case study of the initiatives undertaken by the Directorate of Civil Aviation (DCA) of Namibia over the period 2008 to 2014 in securing talent for aviation safety. The International Civil Aviation Organisation (ICAO) regularly assesses the extent to which member states comply with their safety oversight responsibilities. According to a 1996 report by the ICAO, under the auspices of its Universal Safety Oversight and Security Audit Programme (USOSAP), Namibia's safety oversight was found to be weak, as indicative of the State's inability to guarantee the safety of aircraft operations within the national airspace (ICAO, 1996). One of the significant audit findings was the critical shortage of qualified professionals at the Directorate Civil Aviation (DCA) to effectively perform the State's regulatory and oversight function as contained in the Chicago Convention of 1944. The shortage of qualified professionals resulted in Namibia being unable to respond to its obligations and responsibilities under the Chicago Convention and Namibia's subsequent blacklisting by the ICAO Audit Result Review Board (ARRB). Consequently, a corrective action plan was undertaken. This study examines one aspect of this plan, namely the initiatives that were undertaken to secure the talent required for aviation safety posts. The aim of the research is, from the perspective of talent management, to analyse the corrective action plan of the Directorate of Civil Aviation (DCA), as a process of securing talent for strategic positions in aviation safety in Namibia. This initiative was analysed from the perspective of the fourth stream of talent management, which emphasises securing talent for strategic positions (Collings and Mellahi, 2009; Huselid & Becker, 2011). Taking into account the fact that Namibia was a racially and culturally divided society until about 25 years ago, the study also deals with issues of diversity management as they impacted upon the talent management of the civil aviation industry nationally. Furthermore, the study is located against the background of the Bantu Education System that was provided by the apartheid South African government to Namibians before independence in 1990. The research design of this study involved conducting a case study that followed a deductive approach. Data were collected using multiple methods and sources such as documentation, interviews and archival records. Content analysis was used in the analysis of collected data. The findings of the study showed the talent management strategies that were adopted in managing strategic positions, the challenges encountered and the impact of the programme. The findings were initially discussed from the perspective of stream four of talent management, with its focus on strategic positions in organisations. Some of the findings of the study were in line with this approach to talent management, but certain challenges that were encountered in carrying out the talent management programme could not be addressed from this perspective, thereby exposing the limits of this approach to talent management in an emerging economy like Namibia. Consequently, a proposed model of sustainable talent management for the DCA was developed. From the perspective of this model of sustainable talent management, recommendations were made for practice and further research.
Keywords: Uncatalogued